(-)-Hydroxycitric acid attenuates endoplasmic reticulum stress-mediated alterations in 3T3-L1 adipocytes by protecting mitochondria and downregulating inflammatory markers. (November 2014) - Nisha, V. M.; Priyanka, A.; Anusree, S. S.; Raghu, K. G.
Abstract Endoplasmic reticulum (ER) stress is an emerging potential therapeutic target for metabolic syndrome due to its role in synthesis, secretion, and folding of proteins. It leads to an increased production of reactive oxygen species (ROS) which, along with mitochondrial dysfunction and reduced antioxidant defense, causes chronic cell injury. The present investigation aims to observe the alterations in adipocytes due to ER stress and the protective effect of hydroxycitric acid (HCA), a bioactive from Garcinia species, to develop the same as a nutraceutical. ER stress was induced in mature 3T3-L1 adipocytes by treating them with tunicamycin (2μg/ml) for 18 h. Alterations in cell viability, innate antioxidant system (superoxide dismutase, glutathione peroxidase, and glutathione reductase), mitochondria (membrane potential, biogenesis, and transition pore opening), and inflammatory cytokines (tumor necrosis factor, monocyte chemoattractant protein, interferon-γ, interleukin (IL)-10, IL-6, and IL-1β) during ER stress, and co-treatment with HCA were analyzed. Endocrine function of adipocytes was also assessed by measuring adiponectin and leptin secretion levels. HCA protected the cells from ER stress by improving the antioxidant status and mitochondrial functions. The results validate nutraceutical properties of the edible bioactive, commonly used for culinary purpose. A more detailed study on the mechanism of action of HCA is required for developing it as a therapeutic agent for metabolic syndrome.